Dipole retardation in a mixture of acetamide and calcium nitrate - R. PŁOWIEC; K. ORZECHOWSKI (Archives of Acoustics)
The results of investigations of the dielectric properties of an acetamide and calcium nitrate mixture (x_acetam = 0.7644) are presented. They are to be complementary to ultrasonic and viscoelastic studies made previously [4]. It has been established that two relaxation processes exist. They are referred to the previously described ultrasonic relaxation spectra and retardation in the viscoelastic spectrum.